Dyskeratosis congenita: natural history of the disease through the study of a cohort of patients diagnosed in childhood - Uria-Oficialdegui, M. L.; Navarro, S.; Murillo-Sanjuan, L.; Rodriguez-Vigil, C.; Benitez-Carbante, M. I.; Blazquez-Goñi, C.; Salinas, J. A.; Diaz-de-Heredia, C. (Frontiers in Pediatrics, 2023)
Background Dyskeratosis congenita (DC) is a multisystem and ultra-rare hereditary disease characterized by somatic involvement, bone marrow failure, and predisposition to cancer. The main objective of this study is to describe the natural history of DC through a cohort of patients diagnosed in childhood and followed up for a long period of time. Material and methods Multicenter, retrospective, longitudinal study conducted in patients followed up to 24 years since being diagnosed in childhood (between 1998 and 2020). Results Fourteen patients were diagnosed with DC between the ages of 3 and 17 years (median, 8.5 years). They all had hematologic manifestations at diagnosis, and nine developed mucocutaneous manifestations during the first decade of life. Seven presented severe DC variants. All developed non-hematologic manifestations during follow-up. Mutations were identified in 12 patients. Thirteen progressed to bone marrow failure at a median age of 8 years [range, 3–18 years], and eight received a hematopoietic stem cell transplant. Median follow-up time was 9 years [range, 2–24 years]. Six patients died, the median age was 13 years [range, 6–24 years]. As of November 2022, eight patients were still alive, with a median age of 18 years [range, 6–32 years]. None of them have developed myeloblastic syndrome or cancer. Conclusions DC was associated with high morbidity and mortality in our series. Hematologic manifestations appeared early and consistently. Non-hematologic manifestations developed progressively. No patient developed cancer possibly due to their young age. Due to the complexity of the disease multidisciplinary follow-up and adequate transition to adult care are essential.